The Role of Community Learning Center (CLC) in Providing Nonformal Education Services Based on Entrepreneurship - Rahma, Rezka Arina; Zulkarnain, Zulkarnain; Desyanty, Ellyn Sugeng; Wahyuni, Sri (Journal of Nonformal Education, 2019)
The Community Learning Center (CLC) is an institution of, by and for the community in providing educational services outside of the school system. The existence of CLC institutions is very important because various community learning needs cannot be accommodated in schooling education in the form of training, equality, entrepreneurship programs. Strengthening CLC institutions in providing non-formal education services with entrepreneurship to attract the interest of the community and equip the community with entrepreneurial abilities. This entrepreneurship program is capable of supporting non-formal education programs at CLC. Entrepreneurship-based CLC management is intended to maintain the sustainability of Non-formal Education programs (NFE), provide professional services and establish direct partnerships with the community. The method used in this study is descriptive qualitative. The data was collected using direct interview techniques, observation, and documentation. The data obtained is then analyzed by the procedure of collecting data, reducing data, presenting data, interpreting data, and concluding data. The results of this study indicate that the empowerment of CLC institutions in providing non-formal education services that lead to community empowerment includes as a complement to vocational skills, facilitation, motivation. The results of this study contributed significantly to the development of non-formal education programs in Indonesia.Â Â